Respiratory viruses in exacerbations of chronic obstructive pulmonary disease requiring hospitalisation: a case-control study. Issue 1 (1st January 2003) - Rohde, G; Wiethege, A; Borg, I; Kauth, M; Bauer, T T; Gillissen, A; Bufe, A; Schultze-Werninghaus, G
Abstract : Background: Acute exacerbations of chronic obstructive pulmonary disease (AE-COPD) are a common cause of hospital admission. Many exacerbations are believed to be due to upper and/or lower respiratory tract viral infections, but the incidence of these infections in patients with COPD is still undetermined. Methods: Respiratory syncytial virus (RSV), influenza A and B, parainfluenza 3, and picornaviruses were detected by nested reverse transcription polymerase chain reaction (RT-PCR) in upper (nasal lavage) and lower respiratory tract specimens (induced sputum). In a 2:1 case-control set up, 85 hospitalised patients with AE-COPD and 42 patients with stable COPD admitted for other medical reasons were studied. Results: Respiratory viruses were found more often in sputum and nasal lavage of patients with AE-COPD (48/85, 56%) than in patients with stable COPD (8/42, 19%, p<0.01). The most common viruses were picornaviruses (21/59, 36%), influenza A (15/59, 25%), and RSV (13/59, 22%). When specimens were analysed separately, this difference was seen in induced sputum (exacerbation 40/85 (47%) v stable 4/42 (10%), p<0.01) but was not significant in nasal lavage (exacerbation 26/85 (31%) v stable 7/42 (17%), p=0.14). In patients with AE-COPD, fever was more frequent in those in whom viruses were detected (12/48, 25%) than in those in whom viruses were not detected (2/37, 5%, p=0.03). Conclusion: Viral respiratory pathogens are found more often in respiratory specimens of hospitalised patients with AE-COPD than in control patients. Induced sputum detects respiratory viruses more frequently than nasal lavage in these patients. These data indicate that nasal lavage probably has no additional diagnostic value to induced sputum in cross-sectional studies on hospitalised patients with AE-COPD and that the role of viral infection in these patients is still underestimated.